Pecularities of symmetry detection in polygons with different degree of symmetry - Gurčinienė, Ona; Šoliūnas, Alvydas (Psichologija, 2005)
Though the mirror symmetry is investigated broadly the mechanisms of symmetry perception are not yet known. Most studies of symmetry perception are performed with dot patterns. This paper is devoted to extend the experimental data with different type of stimuli and procedures. The psychophysical experiment was conducted to determine the symmetry and asymmetry detection time and accuracy in the perfectly symmetrical and asymmetrical figures with different degree of symmetry. The figures (plane polygons) were constructed on a base of 3x3 square matrix and covered 5 squares area. The ratio of coincident with noncoincident elements of figures on both sides of axis of symmetry had three different values and indicated the degree of symmetry of asymmetrical figures. The symmetrical and asymmetrical figures were oriented vertically or horizontally and were of white colour on a black background. The exposition duration of figures was defined during the practice session individually for each subject so, that detection accuracy would be approximately 60–90% (it varied from 17 to 300 ms for different subjects). After the figure presentation the white masking square was presented for 500 ms covering the figure. The subject was asked to answer as fast as possible whether the figure was symmetrical or asymmetrical by pressing an appropriate key on a keyboard. Altogether 480 figures were presentated during the experiment that lasted about 40 minutes. The experimental results confirmed the advantage of vertical symmetry over the horizontal, that is the vertically symmetrical figures were detected more accurately and faster than horizontally symmetrical ones. Averaged results of all subjects indicated that the detection accuracy of asymmetry increased and the detection time decreased as the degree of symmetry of asymmetrical figures decreased. Depending on qualitative differences in the symmetry and asymmetry detection the subjects were divided into two groups. Majority of subjects detected asymmetry more accurately and faster than symmetry, and theirs detection time of asymmetry decreased as a degree of symmetry decreased. They detected the small deviation from perfect symmetry more accurately and theirs averaged detection time was shorter than it was for other subjects, which detected symmetry more accurately and faster than asymmetry. Last-mentioned subjects did not discriminate the asymmetrical figures with highest degree of symmetry from symmetrical ones, and the detection time of asymmetry almost did not depend on the degree of symmetry of asymmetrical figures. Detection time of symmetry and asymmetry was shorter for male than female subjects. The implications of individual differences in symmetry and asymmetry detection are discussed.